Health Benefits of Quassin from Quassia amara: A Comprehensive Review of their Ethnopharmacological Importance, Pharmacology, Phytochemistry and Analytical Aspects - Patel, Kanika; Patel, Dinesh K. (Current Nutrition & Food Science, 2020)
Medicinal plants have been indispensable to human life as they are used in food, cosmetics, medicines, nutraceuticals, perfumery, beverages and many more sectors. The medicinal plant contains various important classes of phytochemicals and broadly they are categorized into either primary or secondary metabolite. A large number of modern medicines are mainly derived from plant and other natural sources. Medicinal properties of plants are mainly due to the presence of their secondary metabolite and good examples are salicylic acid, morphine, quinine, vincristin and vinblastine. In spite of the great discovery of allopathic medicine, plant pure phytoconstituents play an important role in the modern medicine. Various plant based medicine are available in the market and people are using it on the basis of the belief that it is safer compared to the allopathic medicine. Furthermore, based on these believes, people use most of the traditional medicines in their routine life for the treatment of numerous disorders and this is called self-medication. Quassia amara plant belongs to Simaroubaceae family which is one of the best examples of the self-medicated plant. Traditionally Quassia amara has antimalarial, stomachic, antianaemic, antibiotics, cytotoxic and antiamoebic activity. Its reproductive, insecticidal, larvicidal and vermifuge properties have been also reported in the literature. Quassinoids are the important phytoconstituents of this plant and are the main bitter principles of Quassia amara too. Quassin is a white crystalline substance and is widely used in Chinese herbal medicine for their bitter taste. The purpose of this review is to gain an understanding of the Quassin and Quassia amara and to present information and knowledge regarding this phytoconstituent. Medicinal uses, pharmacological importance and various bioanalytical methods of Quassin and Quassia amara have been presented in this review. The benefit of this review is to get better understanding and ideas of Quassin and Quassia amara research findings in various disciplines. Furthermore, there is a need to perform more scientific investigation to explore the other beneficial properties of Quassia amara and Quassin.
Keywords: quassin